MIE DARI TEPUNG KOMPOSIT (TERIGU,GEMBILI (Dioscorea esculenta), LABU KUNING) DAN PENAMBAHAN TELUR - STP, MP, Rosida; W, Rizky Dwi (UPN VETERAN JAWA TIMUR, 2012)
Noodles is a very popular food product which is liked by many people. The rare of wheat as a raw material of noodles in Indonesia caused the research to use composite flour (wheat flout, Gembili flour, and pumpkin flour) to make dried noodles.The aim of this research was to determine the effect of the proportion of wheat flour: gembili flour and the addition of eggs to the quality of dried noodles.This research used Completely Randomized Design (CRD) factorial pattern with 2 factors and 3 times repetition. Factor I was the proportion of wheat flour: gembili flour (80:20, 70:30, 60:40). Factor I was the addition of eggs (15%, 20%, and 25%). The best treatment is the proportion of wheat flour: gembili flour (70:30) and the addition of eggs 20% which produces dry noodles with 8.7966% of moisture content, 10.8588% of protein content, 58.8260% of starch content, 25.0062% of elasticity, 52.7117% of water rehydrating capacity, 2.8803% antioxidant activity, total score of texture preference (86), color preference ( 82) and taste preference (71).Keywords : noodles, gembili, wheat, pumpkin, egg